Recommended Common Data Elements for International Research in Long-Term Care Homes: Exploring the Workforce and Staffing Concepts of Staff Retention and Turnover. (May 2019) - Zúñiga, Franziska; Chu, Charlene H.; Boscart, Veronique; Fagertun, Anette; Gea-Sánchez, Montserrat; Meyer, Julienne; Spilsbury, Karen; Devi, Reena; Haunch, Kirsty; Zheng, Nancy; McGilton, Katherine S.
The aim of this review is to develop a common data element for the concept of staff retention and turnover within the domain of workforce and staffing . This domain is one of four core domains identified by the WE-THRIVE ( W orldwide E lements to H armonize R esearch i n Long-Term Care Li v ing E nvironments) group in an effort to establish an international, person-centered long-term care research infrastructure. A rapid review identified different measurement methods to assess either turnover or retention at facility level or intention to leave or stay at the individual staff level. The selection of a recommended measurement was guided by the WE-THRIVE group's focus on capacity rather than deficits, the expected availability of internationally comparable data, and the goal to provide a short, ecologically viable measurement. We therefore recommend to measure staff's intention to stay with a single item, at the individual staff level. This element, we argue, is an indicator of staff stability, which is important for reduced organizational cost and improved productivity, positive work environment, and better resident–staff relationships and quality of care.